The lost art of hospitality : making people feel welcome in your home - Anderson, Alisha ([place of publication not identified] : Concept Curious, 2019)
From the invitation to saying goodbye, you$1 (Bll find inspiration and guidance on planning to plating, budgeting to bringing ideas to life, conversations to curveballs and everything in between.The Lost Art of Hospitality is than more a guide with practical tips, tricks and how-to's on hosting people in your home. It has been written with your heart in mind, offering you a seat at the table - where hearts are dedicated to community, friends & family that desire to make others welcome in their home.Alisha Anderson has been entertaining friends and family in her home for over 25 years and this book is a behind the scenes, practical application style read with ideas, inspirations and concepts to help you rediscover what she calls; the art of hosting people in your home, gathering for meals, parties, conversations and making them feel loved.s
About Alisha -- Bringing ideas to life -- Tablescapes -- Don't break the bank -- Repurposed decorating -- Prep don't stress -- The extra mile -- Presentation wins -- Curveballs -- Hosting the hang -- Keeping conversation going -- Being great company.
Keywords: HOSPITALITY SERVICE